Effect of temperature and pre-treatment on drying and rehydration characteristics of broccoli slices - Doymaz, Ibrahim; Sahin, Medine (SPRINGER, 2016)
The study investigated effects of pre-treatments and air temperature on drying and rehydration characteristics of broccoli slices. Experiments were carried out at four different air temperatures of 45, 55, 65 and 75 degrees C with constant air velocity of 2.0 m/s. It was observed that drying and rehydration characteristics of broccoli slices were influenced by air temperature and pre-treatment. Six different mathematical drying models (Newton, Page, Henderson and Pabis, Logarithmic, Wang and Singh, and Midilli et al.) were evaluated for goodness of fit by comparing their respective R-2, chi(2), and RMSE parameters. The Midilli et al. model showed better prediction compared with the other models and satisfactorily described the drying characteristics of broccoli slices and is applicable under the given experimental conditions. The values of effective moisture diffusivity (D-eff ) fluctuated between 3.27 x 10(-9) and 1.23 x 10(-8) m(2)/s. Activation energy was estimated by an Arrhenius type equation and was 17.14, 32.33 and 35.14 kJ/mol for blanch, citric acid, and control samples, respectively.
Keywords: Broccoli; Effective moisture diffusivity; Hot-air drying; Mathematical modelling; Pre-treatment; KINETICS; QUALITY; FLORETS; IMPACT; Food Science & Technology